Congenital hypertrophy of multiple intrinsic muscles of the foot. Issue 6 (December 2013) - Shiraishi, Tomohiro; Park, Susam; Niu, Atushi; Hasegawa, Hiromi
Abstract Congenital hypertrophy of a single intrinsic muscle of the foot is rare, and as far as we know, only six cases have been reported. We describe a case of congenital anomaly that showed hypertrophy of multiple intrinsic muscles of the foot; the affected muscles were all the intrinsic muscles of the foot except the extensor digitorum brevis or extensor hallucis. Other tissues such as adipose tissue, nervous tissue, or osseous tissue showed no abnormalities. To reduce the volume of the foot we removed parts of the enlarged muscles.